Synthesis of 3-(4-Methyl-phenyl)-2-phenyl-3,4-dihydro-2H-benzo[e][1,3,2]oxazaphosphinine and Its Chalcogenides - Rani, Manju; Kumar Shukla, Davender; Ali Khan, Arif (Asian Journal of Chemistry, 2013)
A simple method for the synthesis of 3-(4-methyl-phenyl)-2-phenyl-3,4-dihydro-2H-benzo[ e][1,3,2]oxazaphosphinine (2) is described. P-Chalcogenides of (2) can be prepared by reacting with S, Se powder in toluene at 110 ºC. Whereas the tungsten pentacarbonyl complex (6) can be prepared by reacting (2) with W(CO)5CH3CN in THF at 20-25 ºC.